Fungsi Kisah Nabi Hud Dalam Tafsir Orientalis: Analisis Komparatif Theodor Noldeke Dan Ignaz Goldziher - Mohammad Fikri Muthohhari; Safi’in Mansur (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Orientalist interpretations of the Qur'an have so far focused more on the great prophets who have parallels in the Judeo-Christian tradition, while the discussion of minor prophets tends to be marginal and fragmentary. This article aims to analyze the function of the story of the Prophet Hud in the Qur'an as understood in orientalist interpretation, focusing on the readings of Theodor Noldeke and Ignaz Goldziher. This research is a literature-based qualitative study with a descriptive-analytical and comparative approach. Data were obtained from the main works of Noldeke and Goldziher that alluded to the prophetic narrative and structure of the Qur'an, especially related to the story of the Prophet Hud. The results of the study show that Noldeke positioned the story of the Prophet Hud as part of the Qur'anic narrative strategy that functions to strengthen the legitimacy of Muhammad's prophetic treatise through historical parallels with previous prophets. Meanwhile, Goldziher emphasizes the didactic and monotheistic function of the story of the Prophet Hud as a means of establishing religious ethics and internalizing the value of monotheism in the early Muslim community. Comparative analysis reveals that although the two have different methodological emphasises, Noldeke and Goldziher both view the story of the Prophet Hud as a narrative construct that has an ideological function, rather than as a stand-alone historical account. This article contributes by expanding the study of orientalist interpretation through an emphasis on the strategic role of the minor prophet in the construction of Qur'anic discourse. Keywords: Tafsir Orientalis, Prophet Hud, Noldeke, Goldziher, Prophetic Stories